Effectiveness of a Computerized Insulin Order Template in General Medical Inpatients With Type 2 Diabetes - Deborah J. Wexler; Peter Shrader; Sean M. Burns; Enrico Cagliero (2010)
OBJECTIVE To determine whether an electronic order template for basal-bolus insulin ordering improves mean blood glucose in hospitalized general medical patients with hyperglycemia and type 2 diabetes. RESEARCH DESIGN AND METHODS We randomly assigned internal medicine resident teams on acute general medical floors to the use of an electronic insulin order template or usual insulin ordering. We measured diabetes care parameters for 1 month on all patients with type 2 diabetes and blood glucose <60 mg/dl or >180 mg/dl treated by these physicians. RESULTS Intervention group patients (n = 65) had mean glucose of 195 ± 66 mg/dl. Control group patients (n = 63) had mean glucose of 224 ± 57 mg/dl (P = 0.004). In the intervention group, there was no increase in hypoglycemia. CONCLUSIONS Access to a computer insulin order template was associated with improved mean glucose levels without increasing hypoglycemia in patients with type 2 diabetes.